Federico Squarcini (ed.), Boundaries, Dynamics and Construction of Traditions in South Asia - Collinson, Hazel (Religions of South Asia, 2014)
Federico Squarcini (ed.), Boundaries, Dynamics and Construction of Traditions in South Asia. London: Anthem Press, 2011. 618 pp. £80. ISBN 978-0-85728-430-3 (hardback).